Personalized ß-lactam dosing in patients with coronavirus disease 2019 (COVID-19) and pneumonia: A retrospective analysis on pharmacokinetics and pharmacokinetic target attainment. Issue 22 (4th June 2021) - Chiriac, Ute; Frey, Otto R.; Roehr, Anka C.; Koeberer, Andreas; Gronau, Patrick; Fuchs, Thomas; Roberts, Jason A.; Brinkmann, Alexander
Abstract : Abstract: Pathophysiological changes are important risk factors for critically ill patients with pneumonia manifesting sub-therapeutic antibiotic exposures during empirical treatment. The effect of coronavirus disease 2019 (COVID-19) on antibiotic dosing requirements is uncertain. We aimed to determine the effect of COVID-19 on ß-lactam pharmacokinetics (PK) and PK target attainment in critically ill patients with a personalized dosing strategy. Retrospective, single-center analysis of COVID-19 ± critically ill patients with pneumonia (community-acquired pneumonia or hospital-acquired pneumonia) who received continuous infusion of a ß-lactam antibiotic with dosing personalized through dosing software and therapeutic drug monitoring. A therapeutic exposure was defined as serum concentration between (css ) 4 to 8 times the EUCAST non-species related breakpoint). Data from 58 patients with pneumonia was analyzed. Nineteen patients were tested COVID-19-positive before the start of the antibiotic therapy for community-acquired pneumonia or hospital-acquired pneumonia. Therapeutic exposure was achieved in 71% of COVID-19 patients (68% considering all patients). All patients demonstrated css above the non–species-related breakpoint. Twenty percent exceeded css above the target range (24% of all patients). The median ß-lactam clearance was 49% compared to ß-lactam clearance in a standard patient without a significant difference regarding antibiotic, time of sampling or present COVID-19 infection. Median daily doses were 50% lower compared to standard bolus dosing. COVID-19 did not significantly affect ß-lactam pharmacokinetics in critically ill patients. Personalized ß-lactam dosing strategies were safe in critically ill patients and lead to high PK target attainment with less resources.